فاعلية مشاهدة مقاطع الأفلام العربية في تعلم المفردات العربية - Nik Nur Hidayah Bahari (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This study aims to explore the effectiveness of watching Arabic films in learning the vocabulary among Arabic language students in the sixth level (LQ 0616) at Quranic Language (Arabic Language) Division at Centre for Languages and Pre-University Academic Development (CELPAD) International Islamic University Malaysia during Semester 2, 2019/2018. It also seeks to find the statistically significance between control group and experimental group in three aspects; number of vocabulary learned, depth of vocabulary knowledge, and the use of vocabulary in the context using Analysis of Covariance (ANCOVA). The researcher has used the Quasi-Experimental approach in conducting the study. The data was collected through pre and post-test and distributed to 60 male and female students. The results of this study found that there is a statistically significant between control group and experimental group in number of vocabulary learned, depth of vocabulary knowledge, and the use of vocabulary in the context. Thus, this study suggests that, watching Arabic films with subtitles might help students in learning new vocabulary in Arabic language as a second language. Finally, the researcher made recommendations and suggestions in teaching and learning Arabic as a second language.